Monetary policy spillovers and emerging market credit: The impact of Federal Reserve communications on sovereign CDS spreads - Ingo Fender; Bernd Hayo; Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
In this paper, we study the effects of US target rate changes and related communications by members of the Federal Reserve Board of Governors on spreads for emerging market sovereign credit default swaps (CDS). Using GARCH models, we find that during the pre-financial crisis sub-sample (April 2002-July 2007) CDS spreads react more to country-specific factors than to US monetary policy news. This finding is reversed during the financial crisis sub-sample (August 2007-December 2009), when US monetary policy actions and communications affect CDS spreads in a notable way. Finally, our analysis suggests that CDS spreads became more prone to spillover effects during the financial crisis.
Keywords: E52; G14; G15; 330; credit default swaps; emerging markets; Federal Reserve communication; financial crisis; policy spillovers; Geldpolitik; Informationsverhalten; Staatliche Information; Spillover-Effekt; Credit Default Swap; Länderrisiko; Risikoprämie; Aufstrebende Märkte; USA; Schwellenländer